Complex furrows in a 2D epithelial sheet code the 3D structure of a beetle horn. Issue 1 (December 2017) - Matsuda, Keisuke; Gotoh, Hiroki; Tajika, Yuki; Sushida, Takamichi; Aonuma, Hitoshi; Niimi, Teruyuki; Akiyama, Masakazu; Inoue, Yasuhiro; Kondo, Shigeru
Abstract The external organs of holometabolous insects are generated through two consecutive processes: the development of imaginal primordia and their subsequent transformation into the adult structures. During the latter process, many different phenomena at the cellular level (e.g. cell shape changes, cell migration, folding and unfolding of epithelial sheets) contribute to the drastic changes observed in size and shape. Because of this complexity, the logic behind the formation of the 3D structure of adult external organs remains largely unknown. In this report, we investigated the metamorphosis of the horn in the Japanese rhinoceros beetleTrypoxylus dichotomus . The horn primordia is essentially a 2D epithelial cell sheet with dense furrows. We experimentally unfolded these furrows using three different methods and found that the furrow pattern solely determines the 3D horn structure, indicating that horn formation in beetles occurs by two distinct processes: formation of the furrows and subsequently unfolding them. We postulate that this developmental simplicity offers an inherent advantage to understanding the principles that guide 3D morphogenesis in insects.